Firm internationalization strategy in the context of digitization: managerial insights based on ai investment (Journal of Economic Research & Business Administration, 2025)
Rapid digitalization has changed how firms organize production, manage information, and operate across national borders, raising growing interest in how digital technology shapes international expansion. While existing studies have discussed the role of digital transformation in firm performance, empirical evidence on how specific digital investments relate to firm internationalization remains limited, particularly in emerging-market contexts.Using panel data from Chinese A-share listed companies between 2015 and 2024, this study examines the relationship between artificial intelligence (AI) investment and firm internationalization. A fixed-effects regression model is employed to account for unobserved firm heterogeneity, and a series of robustness checks are conducted to ensure the stability of the results. Firm internationalization is measured by overseas income, while AI investment captures firms’ engagement in digital transformation.The empirical results show that firms with higher levels of AI investment tend to generate greater overseas income, indicating a positive association between digital investment and internationalization. This relationship remains stable across alternative model specifications and sample adjustments. In addition, firm size and profitability are positively related to internationalization, suggesting that resource availability and financial capacity support overseas expansion. By contrast, firms experiencing rapid growth in the domestic market are less active internationally, reflecting potential trade-offs in strategic focus.Overall, the findings provide firm-level empirical evidence on how digital investment relates to internationalization outcomes. The results also suggest that digital transformation is more likely to support international expansion when it is aligned with firms’ resources, technological capabilities, and organizational structures, rather than treated as an isolated technological initiative.Key words: digital transformation, international management, artificial intelligence, internationalization strategy, Chinese firms.